Exploring The Transformative Zone of Tolerance in Indigenous Education: Insights from Pesantren-Based Services - Akmal Mundiri; Siti Julaiha; M. Abzar Duraesa; Rahimah Embong (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
As an indigenous Indonesian Islamic educational institution, pesantren offers unique services valued by its users. Service quality, oriented toward zero-defect service and user satisfaction, has a unique meaning due to the intertwined differences in satisfaction and value orientations. This study aims to understand the zone of tolerance in Pesantren, the factors that cause tolerance or tolerance of services, and the implications of a zone of tolerance for students. This study uses a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation. The research results show that tolerance zones in Islamic boarding schools encompass tolerance for delays in access, dysfunction in the guidance and counseling process, and limited services. Meanwhile, factors contributing to the emergence of tolerance for service quality include cultural awareness, awareness of limited resources, social class strata, service users’ understanding of environmental realities, and their patient character. The existence of pesantren-based tolerance zones has positive implications, including strengthening the values of independence and adaptability, increasing mental resilience, and fostering a sense of togetherness and solidarity. The study concluded that spaces within the zone of tolerance for service quality in pesantren are among the educational media that strengthen the internalization of core values. The research findings also reveal a gap between service and expectations, encompassing pedagogical mechanisms with transformative functions. Thus, these findings demonstrate a new concept, the Transformative Zone of Tolerance, a space of service tolerance that serves not only as a buffer against dissatisfaction but also as an instrument for students’ character development.